European Small Business Finance Outlook: June 2019 - Helmut Kraemer-Eis; Antonia Botsari; Salome Gvetadze; Frank Lang; Wouter Torfs (European Investment Fund (EIF), 2019)
This analysis provides an overview of the main markets relevant to the EIF. It starts by discussing the general market environment, then looks at the main aspects of equity finance and the guarantee and SME securitisation markets. It also highlights important aspects of microfinance in Europe. Finally, the analysis includes a chapter dedicated to Fintech.
Keywords: 330